104k views
5 votes
How do you solve this?

How do you solve this?-example-1

1 Answer

4 votes

\bf ~~~~~~~~~~~~\textit{negative exponents} \\\\ a^(-n) \implies \cfrac{1}{a^n} \qquad \qquad \cfrac{1}{a^n}\implies a^(-n) \qquad \qquad a^n\implies \cfrac{1}{a^(-n)} \\\\ -------------------------------


\bf \cfrac{2x^{-(7)/(4)}}{4x^{(4)/(3)}}\implies \cfrac{2}{4}\cdot \cfrac{x^{-(7)/(4)}}{x^{(4)/(3)}}\implies \cfrac{1}{2}\cdot \cfrac{1}{x^{(4)/(3)}\cdot x^{(7)/(4)}}\implies \cfrac{1}{2}\cdot \cfrac{1}{x^{(4)/(3)+(7)/(4)}}\implies \cfrac{1}{2}\cdot \cfrac{1}{x^{(16+21)/(12)}} \\\\\\ \cfrac{1}{2}\cdot \cfrac{1}{x^{(37)/(12)}}\implies \cfrac{1}{2x^{(37)/(12)}}
User Geetanjali
by
5.4k points